Kualitas Spermatozoa Mencit yang Terpapar Radiasi Sinar-X Secara Berulang (SPERMATOZOA QUALITY OF MICE EXPOSED TO X-RAYS RADIATION IN REPEATED) - Sudatri, Ni Wayan; Suartini, Ni Made; Sukmaningsih, Anak Agung Sagung Alit; Yulihastuti, Dwi Ariani (Jurnal Veteriner, 2015)
In radiology, X-ray has been used to diagnose disease and therapy. However, behind the technologybenefits provided by the radiation, the negative effects are often debated. The purpose of this study was toinvestigate the effects of repeated radiation on sperm quality mice (Mus musculus L). Thirty- two adultmale mice aged three months were divided into groups P1 (1x 200 rad), P2 (2x200 rad), P3 (3x200 rad) andcontrol irradiated with x-rays according to the experimental design . Spermatozoa quality parametersobserved were : number of spermatozoa, motility, viability and morphology of spermatozoa. The results ofthe Post Hoc LSD tests for significant differences (P>0.05) between the control and treatment showed thatthe X-ray radiation exposure to 1x200 rad, 2x200 rad, and 3x200 rad decreases the motility, viability,normal morphology and number spermatozoa produced compared with controls. This is caused by exposureto X-ray radiation causes the formation of free radicals in the body that damage sperm cells mice. Exposureto X-ray radiation repeatedly lowered the quality of spermatozoa of mice.
Keywords: x rays, sperm quality, male mice